Retrospective analysis of patients with carcinoma cervix in a rural/semi-urban setting in Western India - Ranvijay Singh; Nishitha Shetty; Maryam Naveed; Suraj B Pawar; Sindu Iska; Navya Reddy Alugubelli (Indian Journal of Medical and Paediatric Oncology)
Objectives: To compare the presentation of cervical cancer and the treatment modalities received by the patients at a semi-urban/rural area of Western India with that of published literature from urban centers. Materials and Methods: We conducted a retrospective analysis of patients with cervical cancer who presented at a semi-urban/rural cancer center between 2010 and 2013. A total of 141 patients with the median age of 51 years (25-81) were studied. The demographic and clinical variables included age, annual family income, profession, comorbidities, baseline hemoglobin, prior screening, clinical stage, treatment administered, and complications. The pathological variables included tumor type and grade. Results: In our study, all patients presented with vaginal bleeding. Majority of the patients (51 patients, 37.7%) had Stage 3B disease. Since majority presented at later stages (Stage 3B), chemotherapy-radiotherapy was the most common treatment modality used in our population. On histopathology, 127 patients (90%) had squamous cell carcinoma while 14 patients (10%) had adenocarcinoma. In 96 patients (68%), the tumor grade was not known while it was a high, intermediate, and low grade in 6 (4%), 18 (13%), and 21 (15%) patients, respectively. The follow-up data of our study were not adequate; hence, the long-term survival results could not be presented. Conclusion: Patients in rural India setting present at later stages which could be improved by creating awareness, improving their personal hygiene, and adequate screening.